Nursing strategies for the mechanically ventilated patient - Meitner, Cassandra; Feuerstein, Rachel A.; Steele, Andrea M. (Frontiers in Veterinary Science, 2023)
The goal of this manuscript is to provide a comprehensive and multi-disciplinary review of the best nursing practices of caring for mechanically ventilated patients. By reviewing human medicine literature, the authors will extrapolate procedures that have been found to be most effective in reducing the risk of mechanical ventilation (MV) complications. Paired with review of the current standards in veterinary medicine, the authors will compile the best practice information on mechanically ventilated patient care, which will serve as a detailed resource for the veterinary nursing staff. Written from a nursing standpoint, this manuscript aims to consolidate the nursing assessment of a mechanically ventilated patient, addressing both systemic and physical changes that may be encountered during hospitalization. The goal of this review article is to present information that encourages a proactive approach to nursing care by focusing on understanding the effects of polypharmacy, hemodynamic changes associated with MV, complications of recumbent patient care, and sources of hospital acquired infections. When applied in conjunction with the more technical aspects of MV, this manuscript will allow veterinary technicians involved in these cases to understand the dynamic challenges that mechanically ventilated patients present, provide guidance to mitigate risk, address issues quickly and effectively, and create an up-to date standard of practice that can be implemented.